Hölder Continuity of a Parametric Generalized Variational Inequality - Li-na Wang; Xiao-bing Li (Abstract and Applied Analysis)
By using the classic metric projection method, we obtain sufficient conditions for Hölder continuity of the nonunique solution mapping for a parametric generalized variational inequality with respect to data perturbation. The result is different from the recent ones in the literature and has a strong geometric flavor.